Comprehensive investigation on influence of copper doping on physical properties of CdSe thin films for solar cell applications. (August 2022) - Himanshu; Chasta, G.; Suthar, D.; Thakur, A.; Kannan, M.D.; Dhaka, M.S.
Highlights: Influence of Cu doping on properties of CdSe films is investigated for solar cells. Structural study unveils boost in crystallite size from 38 to 52 nm with Cu doping. Enhanced visible light absorption and refractive index are found for 5% Cu doping. Morphological study showed elongated and nanospherical grains with grain growth. I-V plots confirm Ohmic nature and EDS patterns validate deposition of CdSe:Cu films. Abstract: Incorporation of foreign dopant in CdSe host lattice is fascinating approach to tune absorbance, grain-size, conductivity, morphology, topography and stoichiometric-compositions for absorber layer solar cell applications. Herein, thin films of CdSe:Cu alloys having 1%, 3% and 5% Cu contents are grown using thermal-evaporation technique and subsequently annealed at 350 °C. Structural exploration unveils phase-transformation from (103) orientation of hexagonal to (111) orientation of cubic CdSe at 3% and 5% Cu doping with appropriate substitution of Cd 2+ by Cu 2+ ions at 5% Cu doping. Different Cu concentrations considerably affect optical-response where higher Cu doping leads to augment in refractive-index and visible-light-absorption. PL spectra exhibit two peaks with stronger near-band-edge luminescence at ∼685 nm. Two-dimensional AFM micrographs show spherical-elliptical grains at lower Cu concentration whereas agglomerated-interlinked grains at higher concentration. FESEM micrographs display elongated-nanospherical grains having size in 45-60 nm range. Thus, present investigation offers comprehensive insights for tailoring properties of CdSe films with Cu dopant for solar cells. Graphical abstract: Image, graphical abstract